Traditional Chinese medicine promotes the resorption of herniated intervertebral discs by regulating autophagy and apoptosis - Feng Mao; Xiaoying Ma; Jingyun Chen; Hongwei Li; Zhijia Ma; Feng Dai; Baixue Xu; Jingtao Liu; Hong Jiang; Pengfei Yu (Elsevier, 2022)
Yiqi Huoxue Decoction (abbreviated as YH in this paper) is a well-accepted traditional Chinese medicine formula used for the treatment of lumbar disc herniation (LDH). The main components of YH, such as tetrandrine, astragaloside IV and ferulic acid, have the effects of regulating inflammation and immunity as well as analgesia. Our lab previously reported that YH could promote the accumulation of reactive oxygen species (ROS) in the nucleus pulposus cells. This study was to determine the effect and mechanism of YH on both ruptured and non-ruptured intervertebral disc (IVD). First, we isolated human primary nucleus pulposus cells, then incubated them with 10 μM H2O2 to imitate the condition of oxidative stress in vivo. We found that YH-containing serum could promote the apoptosis and autophagy of nucleus pulposus cells in vitro. Next, we constructed rat models of both ruptured and unruptured disc herniation. The in vivo results showed that YH significantly could promote the number of autophagosomes, proportion of apoptotic cells, and expression levels of autophagy/apoptosis-related proteins in the nucleus pulposus of ruptured IVD. Also, YH could promote the resorption and degeneration of the ruptured IVD. Further, we investigated the molecular mechanism of YH-enhanced resorption of ruptured IVD. The in vitro data suggested that YH could activate ERK/mTOR in nucleus pulposus cells, leading to excessive autophagy and apoptosis while ERK inhibitor U0126 reversed the effect of YH on the ROS content, proportion of apoptotic cells and expression levels of autophagy. Overall, this study has demonstrated that the traditional Chinese medicine Yiqi Huoxue decoction promotes the resorption of herniated IVD via regulating ERK/mTOR-mediated apoptosis/autophagy in the nucleus pulposus cells, which highlights traditional Chinese medicine has a great potential for clinical conservative treatment for lumbar disc herniation.